Metabarcoding clarifies the diet of the elusive and vulnerable Australian tjakura (Great Desert Skink, Liopholis kintorei) - Thuo, David; Macgregor, Nicholas A.; Merson, Samuel D.; Scopel, Dianne; Keogh, J. Scott; Kenny, Jeremy; Williams, Jessica L.; Guest, Tracey; Swan, Shaeleigh; McAlpin, Steve; Joseph, Leo (Frontiers in Ecology and Evolution, 2024)
Accurately quantifying the diet of species has implications for our understanding of their ecology and conservation. Yet, determining the dietary composition of threatened and elusive species in the wild is often difficult. This study presents the first dietary assessment of tjakuṟa (Liopholis kintorei) using non-invasive sampling of scats and high-throughput sequencing techniques. The tjakuṟa in Uluṟu consumed 48 invertebrates, 27 plants, and two vertebrate taxa. Fruit flies (Leucophenga spp.), beetles (Harpalus spp. and Omorgus spp.), mosquitos (Culicidae spp.), termites (Termitidae spp.), spiked mallow (Malvastrum americanum), bush tomatoes (Solanum centrale), and wild turnip (Brassica tournefortii) comprised the majority of the diet. Analysis of similarity revealed that food items did not differ significantly between tjakuṟa age groups, seasons, or time since the last fire, however, adults, hot season, and fire scar of 2018 showed a relatively higher prey diversity. These high similarities in diet composition between age classes and fire scars indicate potential intraspecific competition when food resources are scarce. The diet diversity and potential plasticity observed in this study reflect a dietary ecology influenced by food availability rather than preference. Our study demonstrates that scat DNA metabarcoding is an important complementary tool to conventional scat analysis or indigenous knowledge as most food items we identified were previously not recorded through those methods.